2003
DOI: 10.1021/bi035054a
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Cycle Analysis and Inhibitor Design against Beta-Lactamase

Abstract: Beta-lactamases are the most widespread resistance mechanism to beta-lactam antibiotics, such as the penicillins and cephalosporins. Transition-state analogues that bind to the enzymes with nanomolar affinities have been introduced in an effort to reverse the resistance conferred by these enzymes. To understand the origins of this affinity, and to guide design of future inhibitors, double-mutant thermodynamic cycle experiments were undertaken. An unexpected hydrogen bond between the nonconserved Asn289 and a k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…This mechanism is consistent with substrate modification studies by Mobashery, which suggested that analogues lacking the equivalent nitrogen were trapped in the acyl adduct, as well as inhibition and structural studies that suggested that β-lactams with displaced nitrogens acted as inhibitors. 26, 31 We note that studies of alternative depsipeptides substrates are not easily reconciled with this hypothesis since these substrates lack the lactam nitrogen. 40 That said, analogous roles for the equivalent thiol in these alternative substrates cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism is consistent with substrate modification studies by Mobashery, which suggested that analogues lacking the equivalent nitrogen were trapped in the acyl adduct, as well as inhibition and structural studies that suggested that β-lactams with displaced nitrogens acted as inhibitors. 26, 31 We note that studies of alternative depsipeptides substrates are not easily reconciled with this hypothesis since these substrates lack the lactam nitrogen. 40 That said, analogous roles for the equivalent thiol in these alternative substrates cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Although small‐molecule solution experiments suggested that a Tyr150‐like phenolic group was negatively charged at pH 7,19 NMR studies on the class C β‐lactamase from Citrobacter freundii GN346 suggest that the pKa of Tyr150 is above pH 11 in the apo‐enzyme,20 disfavoring the tyrosinate hypothesis. The substrate‐assisted catalysis model is supported by the observations that certain substrate analogs lacking the equivalent nitrogen were trapped in the acyl complex and that β‐lactam compounds with displaced nitrogens acted as inhibitors 13, 21. Some experiments have also suggested that the pKa of the lactam nitrogen may be between pH 5 and 6, consistent with the proposed general base function 22.…”
Section: Introductionmentioning
confidence: 84%
“…However, Asn289 is not a well conserved residue among class C β-lactamases. The K i of this cephalothin analog increases from 1 nM with the E.coli AmpC to 29 nM with the E. cloacae P99 AmpC which has a Ser289, suggesting that the amino acid at position 289 plays a role for the affinity of compound 5 (47, 58). …”
Section: Discussionmentioning
confidence: 99%
“…Further, the R 1 amide recognition site formed by the interaction of the R 1 carbonyl and Asn152 in the E. coli AmpC differs from our ADC: 5 representation, as this same side chain carbonyl hydrogen bonds with Lys67 (46). These consensus binding sites were compiled exclusively from crystal structures of the E. coli AmpC, and our kinetic data and modeling analyses indicate the ADC β-lactamase may interact differently with boronic acid inhibitors than other class C enzymes (15, 46, 58). Our molecular representations of ADC in complex with the inhibitors were useful for developing hypotheses; however, we remain cognizant of modeling limitations, such as the lack of active site flexibility and the removal of water molecules during the ligand docking protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation